Political connections and cash holdings in financially constrained firms: evidence from top 500 firms in Malaysia - Kweh, Qian Long; Irene, Wei Kiong Ting; Noor Azlinna, Azizan; Norazlin, Ahmad (Inderscience Enterprises Ltd., 2021)
This study examined the association between political connections and corporate cash holdings, with a focus on financially-constrained companies. Using a unique dataset of the top 500 publicly listed companies in Malaysia as determined by market capitalization for the years 2001-2004, this study measured political connections based on informal ties and government supports. The empirical results of this study show that companies with financial constraints have a lower level of cash holdings, while politically connected companies hold more cash. However, politically connected companies with financial constraints hold more cash. Taken together, this study shows that financially constrained companies are relatively conservative in their cash holdings when they are politically connected even though they are generally perceived as risky by investors, consistent with precautionary motives. The outcome of this study should prove useful in assessing the potential economic consequences to the business environment of politically connected companies, especially in shaping corporate policy.